Amperometric Determination of Bismuth Using Gallacetophenone Phenylhydrazone with the Structural Elucidation of Complex - D. Venkataramana Reddy; A. Varada Reddy (E-Journal of Chemistry)
Gallacetophenone phenylhydrazone (GPPH) has been used as an analytical reagent for amperometric determination of bismuth. Bismuth is quantitatively determined by GPPH at pH 3.0-6.0. After studying the polarographic behaviour of GPPH and bismuth(III) at dropping mercury electrode (DME), applied potential was fixed at -0.4v vs. saturated calomel electrode (SCE). The method was applied for the determination of bismuth in wood’s alloy. The composition of the complex corresponds to the formula Bi(C14 H14 O3 N2)2. The structure of the complex was arrived from the micro analytical data of the solid complex, thermogravimetric and differential thermal analysis curves and also from the infrared spectra of the complex.